Fintech Dan Keberlanjutan Usaha Mikro : Studi Analisis Pada Peer To Peer Lending - Nurjanah; Ar-Royyan Ramly; Zulhilmi (IAIN Langsa, 2024)
The development of MSMEs is needed for Indonesia's economic growth. However, the problem of Micro that often occurs is in the source of capital. The difficulty of MSMEs with micro categories to obtain financing facilities at financial institutions has resulted in the development of innovation and production being hampered. The presence of fintech is one alternative in accessing finance such as loans on peer to peer lending flatforms. The purpose of this study is to see the role of peer to peer lending for the sustainability of Micro in Langsa City. The method used was qualitative descriptive. The results showed that the presence of peer to peer lending is very helpful for Micro in Langsa city that experience a lack of capital or funds to continue their business activities, although the loan period given is only a short time, which is a month. Then, the existence of Peer to peer lending plays a role in continuing the Micro business in the city of Langsa, even playing a role in developing the business for the better.